Kajian Hukum Islam Terhadap Kebijakan Pemerintah Atas Pemberian Kuota Lebih Kepada Jemaah Haji - Fadhilla Ilham Mulkin; La Ode Angga; Sabri Fataruba (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Hajj is the fifth pillar of Islam which is a once-in-a-lifetime obligation for every Muslim who is able to fulfill it.Purposes of the Research: Knowing and analyzing about the provisions of Islamic law in carrying out the pilgrimage. Government policy in the implementation of hajj quotas.Methods of the Research:  This research is included in library research, namely research carried out using literature (library). The author reads and takes theory from books related to the problem under study and then concludes the results of various kinds of research.Results of the Research: The results of the study show that the provisions of Islamic law in carrying out the Hajj, namely the Islamic Shari'a, oblige Hajj for every mukallaf, once in a lifetime for both men and women who have the ability to carry it out. All scholars agreed to stipulate that Hajj is not repeated, it is obligatory only once for a lifetime unless it is prescribed. Apart from the one that is obligatory, it is considered Sunnah more than once. Government policy in organizing Hajj quotas, namely the opening of hajj registration throughout the year, causes a prolonged waiting list for hajj. This is the cause of long queues of pilgrims who want to perform the Hajj because the Ministry of Religion always opens registration. Therefore, the queue becomes long and disorganized.